Study of the technical and tactical variables determining set win or loss in top-level European men`s volleyball - Rodriguez-Ruiz, D.; Quiroga, M. E.; Miralles, J. A.; Sarmiento, S.; de Saa Y.; Garcia-Manso, J. M. (Journal of Quantitative Analysis in Sports, 2011)
This study analyzes the terminating actions (serve, attack, block and opponent error) resulting in point scoring for each team. These actions are then taken as reference indicators for observing the possibility of winning or losing a set in an elite men`s volleyball competition. A total of 45 matches were studied at the European Men`s Volleyball Championship held in September 2009 in Izmir and Istanbul (Turkey). Recordings were made of a number of game actions in a total of 168 sets. Analysis of these sets showed 132 ending in 25 points (78.57 percent) and 36 sets in more even matches (21.43 percent): 27 ending in more than 25 points (16.07 percent) and nine fifth or tie break sets (5.36 percent). Statistical analysis showed attacking to be the highest point-scoring technical action, but as matches became more even (sets with more than 25 points, or fifth and tie break sets), points scored by blocking became decisive for attaining victory in top-level competition. The number of errors made by each team is considerably lower at this level and points achieved through serving tend to be even.